Biology of Plassey Borer, Chilo tumidicostalis (Hampson) (Crambidae: Lepidoptera) - Vishwajeet; Kumar, Anil (International Journal of Economic Plants, 2024)
The experiment was conducted during June to November of 2023 at Bio-control laboratory of Sugarcane Research Institute, Pusa, Samastipur, Bihar, India. The infestation of the Plassey borer started in the month of June and remained prevalent till November month in the field. The infested canes were brought to the laboratory for biological studies. Biological studies of Chilo tumidicostalis Hampson (Crambidae; Lepidoptera) revealed that the female lays eggs in 3–4 batches which averaged 410.64±45.21 eggs per female. The adult female preferred to lay eggs on the live plants only. The incubation period of the eggs was 7.05±0.60 days with hatching percentage as 97.56±0.90%. There was a total of 5 larval instars and the duration of first, second, third, fourth and fifth larval instars were 3.20±0.52, 3.7±0.47, 4.75±0.79, 6.05±0.69 and 6.35±0.67 days, respectively. The pupa and adult showed sexual dimorphism and variation in duration of pupal and adult period. The length of the male and female pupa was26.78±0.10 and 32.85±0.07 mm, respectively. The length of the adult male and female was 11.62±0.15 and 12.74±0.24 mm, respectively. The width of the adult male and female was 24.31±0.63 and 28.73±0.78 mm, respectively. The average pupal period of male and female was 7.25±1.21 and 8.1±1.37 days, respectively. Also, the adult male and female longevity was 3.9±0.64 and 4.8±0.77 days, respectively. The sex ratio was found to be 1:1.24 (male:female).